The role of the residual bitumen in the gas storage capacity of mature lacustrine shale: A case study of the Triassic Yanchang shale, Ordos Basin, China. (January 2016) - Xiong, Fengyang; Jiang, Zhenxue; Chen, Jianfa; Wang, Xiangzeng; Huang, Zhilong; Liu, Guoheng; Chen, Feiran; Li, Yirun; Chen, Lei; Zhang, Lixia
Abstract: The role of the residual bitumen in the shale gas storage capacity is investigated for potential terrestrial shale gas reservoirs in the Yanchang area, southern Ordos Basin, China. The Upper Triassic organic-rich Yanchang shales comprise of thermally mature Chang 7 Shale (average TOC 5.12 wt.%, Type I–II1 kerogen, Tmax 443–458 °C, Ro 0.83%–1.02%) and relatively mature Chang 9 Shale (average TOC 4.40 wt.%, Type I–II1 kerogen, Tmax 443–476 °C, Ro 0.88%–1.10%). The mineralogy of Yanchang shales is dominated by clay minerals (average 48.85%) and quarts (average 31.7%). A series of low pressure nitrogen adsorption/desorption and high pressure methane sorption experiments were conducted on pretreated fresh drilling cores (including three groups of core samples: one original group, one group extracted by dichloromethane and the other group extracted by trichloromethane) selected from Yanchang shales to demonstrate the role of the residual bitumen in the shale gas potential. Low pressure nitrogen sorption method was used to elucidate the effect of the residual bitumen on the pore structure of Yanchang Shales. The results show that the specific surface area and pore volume and pore surface area of shale samples after the extraction greatly increase and their growth was closely related with pores of >30 nm and <10 nm respectively. A negative correlation between the surface area and TOC was observed widespread in Yanchang shales, indicating that the residual bitumen that blocks the pores and pore-throats dramatically influences the methane sorption capacity in the mature shales. Based on nitrogen adsorption/desorption isotherms, ink-bottle-shaped micropores and mesopores likely acting as narrow necks of those pores well developed and were most likely influenced by the residual bitumen, which is favorable for adsorption accumulation but disadvantageous for the seepage of shale gas. The methane sorption isotherms measured on moisture-equilibrated shale samples suggest that the dissolution in the residual bitumen could be an important gas storage mechanism in Yanchang low mature lacustrine shales. Highlights: The role of the residual bitumen was investigated for the low mature shale. A negative relationship between TOC and surface was ascribed to the residual bitumen. The growth of pore volume and area is closely related with pores of >30 nm and <10 nm respectively. The dissolution mechanism could be significant for the terrestrial mature shale.